2015
DOI: 10.1021/acssynbio.5b00193
|View full text |Cite
|
Sign up to set email alerts
|

Slowing Translation between Protein Domains by Increasing Affinity between mRNAs and the Ribosomal Anti-Shine–Dalgarno Sequence Improves Solubility

Abstract: Recent studies have demonstrated that effective protein production requires coordination of multiple cotranslational cellular processes, which are heavily affected by translation timing. Until recently, protein engineering has focused on codon optimization to maximize protein production rates, mostly considering the effect of tRNA abundance. However, as it relates to complex multidomain proteins, it has been hypothesized that strategic translational pauses between domains and between distinct individual struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 32 publications
(73 reference statements)
0
26
0
Order By: Relevance
“…Although their impact on translation rate in vivo now appears smaller than previously thought [25,71], internal SD sequences are disfavored in E. coli coding sequences [24], possibly due to their negative effect on translation elongation rate. Consistent with this, introducing SD sequences within coding sequences has been shown to negatively impact protein accumulation [72]. …”
Section: Other Mechanisms To Control Translation Ratementioning
confidence: 81%
“…Although their impact on translation rate in vivo now appears smaller than previously thought [25,71], internal SD sequences are disfavored in E. coli coding sequences [24], possibly due to their negative effect on translation elongation rate. Consistent with this, introducing SD sequences within coding sequences has been shown to negatively impact protein accumulation [72]. …”
Section: Other Mechanisms To Control Translation Ratementioning
confidence: 81%
“…This is due to several constraints operating to optimize many important biological features such as expression level (Guimaraes, Rocha & Arkin, 2014), translational accuracy (Zaher & Green, 2009), protein solubility (Vasquez et al, 2016), folding accuracy (Sauna & Kimchi-Sarfaty, 2011; Spencer et al, 2012; Bali & Bebok, 2015), and protein stability, among others. In this sense, it has been shown that codon usage in E. coli is biased to reduce the cost of translational errors (Stoletzki & Eyre-Walker, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the compact nature of bacterial genomes, the translation initiation site of many genes within operons will occur within the 3′ terminus of the preceding coding sequence. Further, the presence of multiple translation initiation sites may serve a regulatory role for certain proteins, allowing for the production of distinct isoforms depending on the N-terminal sequence or controlling protein folding rates (Ozin et al 2001; Fluman et al 2014; Schrader et al 2014; Vasquez et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…SD sequence-mediated pauses have now been documented for several bacterial species and independent ribosomal profiling datasets (Li et al 2012; Liu et al 2013; Schrader et al 2014). Studies have built on these results by showing SD-associated pauses in vitro , negative effects of SD sequences on protein production in engineered sequences, enhanced solubility of recombinant proteins via rational insertion of SD sequences at protein domain boundaries, and enrichment of SD sequences following transmembrane domains of natural sequences (Agashe et al 2013; Chen et al 2014; Chevance et al 2014; Fluman et al 2014; Vasquez et al 2015). …”
mentioning
confidence: 99%